The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2147/amep.s147950
|View full text |Cite
|
Sign up to set email alerts
|

Levers of change: a review of contemporary interventions to enhance diversity in medical schools in the USA

Abstract: A growing body of research illustrates the importance of aligning efforts across the operational continuum to achieve diversity goals. This alignment begins with the institutional mission and the message it conveys about the priorities of the institution to potential applicants, community, staff, and faculty. The traditional themes of education, research, and service dominate most medical school mission statements. The emerging themes of physician maldistribution, overall primary-care physician shortage, diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 33 publications
0
84
0
1
Order By: Relevance
“…[12][13][14][15][16] Collaboration with local HBCUs and increased recruitment of Black students, faculty, and staff will provide students more sense of belonging and contribute to the critical mass that is needed to make meaningful change. 17,18 Programs, such as the medical school pipelines at Wayne State University as well as Southern Illinois University Schools of Medicine, have been successful in matriculating and supporting diverse students. 19,20 A cascading mentorship program can promote an inclusive climate by providing academic and social support to students at different levels of education and from a variety of backgrounds.…”
Section: Researchers' Recommendationsmentioning
confidence: 99%
“…[12][13][14][15][16] Collaboration with local HBCUs and increased recruitment of Black students, faculty, and staff will provide students more sense of belonging and contribute to the critical mass that is needed to make meaningful change. 17,18 Programs, such as the medical school pipelines at Wayne State University as well as Southern Illinois University Schools of Medicine, have been successful in matriculating and supporting diverse students. 19,20 A cascading mentorship program can promote an inclusive climate by providing academic and social support to students at different levels of education and from a variety of backgrounds.…”
Section: Researchers' Recommendationsmentioning
confidence: 99%
“…A piecemeal approach results in an ineffective, siloed approach (67). Married with this, is the extension of accountability in order to encourage intentional support (68).…”
Section: ) Responsibility and Accountabilitymentioning
confidence: 99%
“…Greary et al showed how sharing postgraduate medical (residency) diversity recruitment data with training program directors led to significant annual improvements in applicant and selection diversity (70). National dissemination of HEE recruitment data and individual Trust recruitment data, can also allow for benchmarking (68) and identification of specialities and organisations most in need of peer review and reform.…”
Section: ) Data Measurement and Disseminationmentioning
confidence: 99%
See 2 more Smart Citations